2008
DOI: 10.1161/circep.108.776120
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death and Defibrillators in Transposition of the Great Arteries With Intra-atrial Baffles

Abstract: Background-Transposition of the great arteries with intra-atrial baffle repair is among the congenital heart defects at highest risk of sudden death. Little is known about mechanisms of sudden death and the role of implantable cardioverter defibrillators. Methods and Results-We conducted a multicenter cohort study in patients with transposition of the great arteries to determine actuarial rates of implantable cardioverter defibrillator shocks, identify risk factors, assess underlying arrhythmias, and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(142 citation statements)
references
References 31 publications
5
130
0
7
Order By: Relevance
“…Khairy et al reported data from tetralogy of Fallot and transposition of the great arteries patient populations, demonstrating detection rates in patients receiving an appropriate shock of 213 bpm and 222 bpm, respectively. 34,81 Additionally, in a population of ICD patients with Brugada syndrome, the mean detected tachycardia rate in appropriate shocks was 335 bpm, with the suggestion that a single VF zone at 222 bpm would reduce IS by 70%, although it could potentially lead to the missing of appropriate shocks in 1.7% of patients. 82 The frequency of use of ATP and its effectiveness in this population is not well known, although some authors have found the success rate to be low, and have advocated against its routine use.…”
Section: Device-based Interventions In Pediatric and Chd Patientsmentioning
confidence: 99%
“…Khairy et al reported data from tetralogy of Fallot and transposition of the great arteries patient populations, demonstrating detection rates in patients receiving an appropriate shock of 213 bpm and 222 bpm, respectively. 34,81 Additionally, in a population of ICD patients with Brugada syndrome, the mean detected tachycardia rate in appropriate shocks was 335 bpm, with the suggestion that a single VF zone at 222 bpm would reduce IS by 70%, although it could potentially lead to the missing of appropriate shocks in 1.7% of patients. 82 The frequency of use of ATP and its effectiveness in this population is not well known, although some authors have found the success rate to be low, and have advocated against its routine use.…”
Section: Device-based Interventions In Pediatric and Chd Patientsmentioning
confidence: 99%
“…16,25 Inducible VAs at EPS and high ventricularectopy burden on ambulatory cardiac monitoring have not been associated with SCD in patients with TGA in studies to date. 25,28 Additionally, risk factors for malignant arrhythmias in the L-TGA population have been poorly studied to date, although systemic right ventricular dysfunction is accepted as a predictor of adverse outcomes and SCD.…”
Section: Icd Use For the Prevention Of Scdmentioning
confidence: 99%
“…We observed these 2 clinical features more often in patients with abnormal MTWA, though only pulmonary hypertension was confirmed to increase the probability of this phenomenon. Sub-pulmonary ventricle pressure overload along with cyanosis-related tissue hypoxia, as well as segmental dilation and tortuosity of the coronary arteries typical for increased blood viscosity lead to the myocardial fibrosis creating a substrate for ventricular arrhythmia [28,29].…”
Section: Patientsmentioning
confidence: 99%